Implementation of Early Childhood Learning during the Covid-19 Pandemic in Kindergarten Children Mamba'ul Bajubang, Bajubang District - Yennizar Yennizar; Dini Kausari; Ratna Ningsih; Buschhaus Avinash; Bevoor Bevoor (P3M IAI Nusantara Batang Hari, 2022)
The condition of the corona virus outbreak makes children less than optimal in gaining knowledge, because learning that is usually done at school must be done online. The purpose of this study is to find out how the obstacles are and how to overcome obstacles in the implementation of early children’s learning during the covid 19 pandemic at Mamba'ul Ulum Kindergarten Bajubang. This research uses qualitative method, with data collection techniques, observation, interviews and documentation. The respondents in this study are principals, teachers and parents of students. The result of this study is that the implementation of early children’s learning during the COVID-19 pandemic at Mamba'ul Ulum Kindergarten Bajubang is carried out in accordance with the RPPH (Daily Lesson Plan) which is made simpler containing identities, including: theme, sub-theme, day, date and activities to be carried out. Then in the implementation of learning all teachers take turns every day making learning videos that are in accordance with the RPPH (Daily Lesson Plan). The video is a guide for parents at home. Obstacles faced by parents who do not have android mobile phones, lack of parental understanding of early children’s learning, learning outcomes are less than optimal because teachers cannot see directly the process of activities carried out by children. Efforts to overcome problems in early children’s learning during the COVID-19 pandemic at Mamba'ul Ulum Kindergarten Bajubang are by providing additional explanations for learning activities by giving understanding continuously and providing reinforcement to parents.